Perceived role of therapeutic footwear in the prevention of diabetic foot ulcers - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:There is a paucity of literature about the status of therapeutic footwear and their role in prevention of diabetic foot ulcers in Nigeria. The purpose of this study is thus 2-fold. (1) To determine the perceived role of therapeutic footwear in the prevention of foot ulcers among patients with diabetes mellitus, (2) to establish strategies that will encourage the use of therapeutic footwear in the prevention of diabetic foot ulcers.Materials and Methods:This cross-sectional study was carried out among patients with diabetes mellitus in Kaduna state, between December 2012 and March 2013. All the participants in this study had a history of foot ulceration. Exclusion criteria were patients with amputations and non-ambulatory status. Pre-tested questionnaires were used to collect data. The questionnaire was divided into four sections. The first section illustrates the demographics of the respondents. The second section explores the anatomic location of diabetic foot ulcers. The third section evaluates the type of regular footwear worn and experience of participants. The fourth section explores the awareness of respondents regarding therapeutic footwear features. Simple descriptive statistics were used; frequency with percentage distribution for categorised variables.Results:The anatomic subunit in the plantar surface with the highest number of ulcer was the phalanges 23% in males and 26% in females. In the dorsolateral surface, the phalanges 22% and 17% were the most common location in males and females, respectively. Slippers were regularly worn by 71% of respondents, whereas only 1% of respondents were reported to wear therapeutic footwear. More than 75% of respondents were willing to use footwear, as well as buy therapeutic footwear.Conclusion:Majority of the patients are reported to have foot ulcers located on the phalanges and these are related to the wearing of inappropriate footwear. However, they are willing to use therapeutic footwear if recommended by a physician.